Investigation of ZnTiO3/TiO2 composites and their application in photocatalysis - Pei, Zhenzhao; Wang, Pei; Li, Zhiguo (European Journal of Chemistry, 2019)
In this work, we report that ZnTiO3/TiO2 composites, which were synthesized by hydrothermal method possessed photocatalytic and potential spraying properties. The obtained ZnTiO3/TiO2 composites were characterized by scanning electron microscopy (SEM) and X-ray diffraction techniques (XRD). Photocatalytic activities of ZnTiO3/TiO2 composites were evaluated by using Rhodamine B (RhB) as a model pollutant under visible light irradiation. The experimental results showed that the as-prepared ZnTiO3 (2%)/TiO2 composite exhibited better photocatalytic activity than that of pure TiO2.